2010
DOI: 10.1111/j.1399-5448.2010.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the age of onset of type 1 diabetes and the subsequent development of a severe eating disorder by female patients

Abstract: The development of type 1 diabetes in preadolescence or adolescence seems to place girls at risk for the subsequent development of AN or BN. Careful attention should be paid to these high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 26 publications
1
28
0
1
Order By: Relevance
“…Very recently, Acres et al [243] and Hornig and Lipkin [104] hypothesize that AN is an autoimmune disease and may also be associated with major histocompatibility complex (MHC) gene polymorphisms. Indeed, the development of type 1 diabetes in adolescence seems to place girls at risk for the subsequent development of AN and BN [244, 245]. Thus, autoimmune disorders are associated with increased secretion of leptin, whereas AN and BN are conditions of reduced leptin production.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Acres et al [243] and Hornig and Lipkin [104] hypothesize that AN is an autoimmune disease and may also be associated with major histocompatibility complex (MHC) gene polymorphisms. Indeed, the development of type 1 diabetes in adolescence seems to place girls at risk for the subsequent development of AN and BN [244, 245]. Thus, autoimmune disorders are associated with increased secretion of leptin, whereas AN and BN are conditions of reduced leptin production.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that poor control in girls who were diagnosed early may reflect deterioration of glycemic control associated with longer disease duration rather intentional than insulin omission for weight loss. The age of onset of type 1 diabetes mellitus and shorter disease duration were reported to be associated with excess risk for subsequent development of severe eating disorders in female patients …”
Section: Discussionmentioning
confidence: 99%
“…Providers must pay special attention to disordered eating behaviors, even those that are sub-threshold for diagnostic criteria [8]. According to the Center for Disease Control's Youth Risk Behavior Surveillance, a national survey of risk behaviors of high school students, 45% of high school students reported trying to lose weight.…”
Section: Prevalence In General Population and In Those With Type 1 DImentioning
confidence: 99%
“…Adolescents' frequent use of social media may also increase their risk for disordered eating behavior, as it places importance on appearance and facilitates social comparisons [20]. In addition, one study found that females diagnosed with type 1 diabetes between the ages of 7 and 18 years were at a significantly higher risk for developing an eating disorder than those who were diagnosed with diabetes in either young childhood or early adulthood [8]. Thus, it is imperative that health care providers are aware of the increased risk of eating disorder in this age group.…”
Section: Risk Factorsmentioning
confidence: 99%